Relationship between job satisfaction and organizational commitment among employees of Development Finance Institutions (FDIS) in Malaysia - Mohd Othman, Fazilah; Hanafi, Norshafizah; Ridzuan, Zaharin (2014)
This study examined the relationship between the five dimensions of job satisfaction of the work itself, supervision, co-workers, promotion and salary satisfaction, with a dependent variable of organizational commitment. This study was conducted in SME Bank, one of the development finance institution (DFI) in Malaysia. Based on the data by Hewitt Associates, the turnover rate in banking and financial services in Malaysia is the second largest. High turnover among employees might jeopardize strategic plans to achieve organizational objectives.When an organization loses its critical people, there might be a number of negative impacts like reduction in overall level of innovation and quality of customer services.Therefore, organization commitment plays a very critical role in order to reduce the employees’ turnover. For this purpose, data were obtained from a sample of 150 employees in eight branches of SME Bank. Using descriptive, correlation, and multiple regression analyses, the results showed that all five elements of job satisfaction have a significant relationship towards organizational commitment.However, the relationships are rather weak, except for the work satisfaction element. Hence, SME Bank could identify and explore these elements to enhance their employees’ job satisfaction in order to promote organizational commitment.